Degradation of Cyanophycin by Sedimentibacter hongkongensis Strain KI and Citrobacter amalonaticus Strain G Isolated from an Anaerobic Bacterial Consortium - Obst, Martin (American Society for Microbiology, 2005)
Using a combination of various enrichment techniques, the strictly anaerobic, gram-positive, endospore-forming bacterium Sedimentibacter hongkongensis strain KI as revealed by 16S rRNA analysis and the gram-negative enterobacterium Citrobacter amalonaticus strain G as revealed by physiological tests were isolated from an anaerobic cyanophycin (CGP)-degrading bacterial consortium. S. hongkongensis strain KI is the first anaerobic bacterium with the ability to hydrolyze CGP to β-Asp-Arg and β-Asp-Lys dipeptides, as revealed by electrospray ionization-mass spectrometry and reversed-phase high-performance liquid chromatography analysis. However, these primary accumulated hydrolysis products were only partially used by S. hongkongensis strain KI, and significant growth on CGP did not occur. On the other hand, C. amalonaticus strain G did not degrade CGP but grew on the β-linked iso-dipeptides formed in vitro by enzymatic CGP degradation or in vivo by metabolic activity of S. hongkongensis strain KI. Dipeptide utilization occurred at the highest rate if both strains were used in cocultivation experiments with CGP, indicating that cooperation between different bacteria occurs in anaerobic natural environments for complete CGP turnover. The amino acids obtained from the cleavage of dipeptides were fermented to ethanol, acetic acid, and succinic acid, as revealed by gas chromatographic analysis and by spectrophotometric enzyme assays.